Pancreatic cysts in general population on ultrasonography: Prevalence and development of risk score - Soroida, Yoko; Sato, Masaya; Hikita, Hiromi; Hagiwara, Shu; Sato, Mamiko; Gotoh, Hiroaki; Kato, Sachiko; Iwai, Tomomi; Yamazaki, Tsutomu; Yatomi, Yutaka; Sasano, Tetsuo; Ikeda, Hitoshi (Journal of gastroenterology, 2016)
Background Pancreatic cysts are related to the presence of ductal adenocarcinomas elsewhere in the pancreas, and are also associated with an increased risk of pancreatic adenocarcinoma in the future. Most of the previous studies that investigated the prevalence of pancreatic cysts focused on patients within a hospital or out-patient setting, which may not be representative of the general population. We investigated the prevalence and predictive factors for the presence of pancreatic cysts within a large number of subjects via general health examination. Methods Between December 2007 and December 2013, a total of 5198 subjects were enrolled that underwent ultrasonography (US) on general health examination. We established a scoring system for predicting the presence of one or more pancreatic cysts using a split-sample method. Results Among the enrolled subjects, the prevalence of a pancreatic cyst was 3.5 %. In multivariate analysis, the prevalence was significantly increased with older age, female sex, and the presence of gall bladder adenomyomatosis (GB-ADM). Based on multivariate analysis in the training sample ( n = 2,599), we established the scoring system consisting of age, sex, and the presence of GB-ADM to predict the presence of pancreatic cysts. This scoring system was validated in the testing sample ( n = 2,599) and produced an area under the curve of 0.711. Conclusions The prevalence of pancreatic cyst detected by US was 3.5 % in the general population, and increased with age, female sex, and the presence of GB-ADM. A new scoring system developed in the present study may help to identify better candidates for further examination when the pancreas is not visible by US.